CBCT Based Comparison of Pharyngeal Airway Area and Volume in patients with Angle’s Class I and Class II Malocclusion: A Retrospective Study - Fareeha Bokhari, Usman Yousaf, Fatima Qayyum, Ayesha Jamil, Mariam Jameel (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To ascertain if there was any association between dental malocclusion and narrow/constricted pharyngeal airway. Methods: It was a retrospective study and cross-sectional in design. Oropharyngeal airway volume and regional area for 58 patients having either Class I or Class II Angles malocclusion were evaluated on the CBCT scans. Results: Oropharyngeal airway volume and area among Angles class I and Class II patients was found to have no statistical difference. There was however statistical difference in the oropharyngeal regional area of male and female patients (t=2.395, p=0.020) with male patients having greater oropharyngeal regional area than female patients. Conclusion: In summary, this research concludes that Angles Class I or Class II malocclusion does not influence oropharyngeal airway volume or area. Gender had no impact on the size of airway volume but had significant influence on the oropharyngeal regional area with male patients having greater oropharyngeal area than females. Keywords: Oropharyngeal airway, CBCT, Class I Malocclusion, Class II Malocclusion